β-Alanine Supplementation and Its Impact on Physical Performance: A Literature-Based Review - Kozicki, Maciej Jakub; Zienkiewicz, Damian; Kostro, Julia Maria; Makulec, Gabriela; Domosud, Karolina; Papież, Magdalena; Jędra, Zofia; Libera, Anna; Bartkiewicz, Karolina; Novik, Lizaveta (Quality in Sport, 2026)
Purpose of research: This literature-based review synthesized the current evidence regarding the effects of β-alanine (BA) supplementation on human physical performance. The review focused on BA as the rate-limiting precursor for intramuscular carnosine synthesis and evaluated its ergogenic impact across various exercise modalities and durations. Research materials and methods: A structured literature search was conducted in major scientific databases, including PubMed, for English full-text articles available through 2025. Only Meta-Analyses, Systematic Reviews, and Randomized Controlled Trials were included, examining BA supplementation in human athletes or trained individuals compared with a placebo or control condition. Basic results: Chronic BA supplementation significantly increases muscle carnosine content and enhances intramuscular buffering capacity, delaying the onset of fatigue during high-intensity exercise. The most robust performance benefits are observed in efforts lasting approximately 1–4 minutes, with supplemental improvements noted in activities up to 10 minutes. BA also supports improvements in training volume and resistance to fatigue. Paresthesia remains the most commonly reported side effect. Conclusions: β-alanine is an evidence-based ergogenic aid that improves performance in high-intensity efforts requiring substantial buffering capacity. Chronic, divided dosing provides the greatest effectiveness.